POLA KESALAHAN PENGERJAAN SOAL CERITA MATEMATIKA SISWA SEKOLAH DASAR BERBASIS GENDER - Stenly Adinda Putri Budiyanto; Muhammad Abduh (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Errors in the work on fractional material metamatics are still commonly found in elementary schools but no one has made a pattern of errors that are often experienced by male students and female students in grade IV elementary schools, therefore the purpose of this study is to find out the pattern of miswork on fractional material stories in elementary schools. grade IV elementary school students by gender. The error analysis pattern uses Newman's theory with five types of errors namely   reading errors, comprehention errors, transformation errors, process skill errors, and errors in writing the final answer conclusion (Endcoding Errors).  The subjects in this study amounted to 48 grade IV elementary school students with 24 male students and 24 female students.  Qualitative case studies were used in this study using data collection techniques in the form of documentation of question work and interviews. The transkrip results of documentation analysis and transkrip interviews were then used to make patterns of miswork on grade IV students based on gender using the help of the Nvivo 12 plus application by codifying to make project map outputs in order to obtain patterns of errors in working on questions based on gender, namely the pattern of  male students and students  Women who produce  patterns of more differences in error patterns than the similarity of patterns of work errors between  male students and  female students in grade IV elementary schools.